Assembly of Schizosaccharomyces cryophilus chromosomes and their comparative genomic analyses revealed principles of genome evolution of the haploid fission yeasts - Lajos Ács-Szabó (Nature Portfolio, 2018)
Abstract The fission yeast clade, which has a distinct life history from other yeasts, can provide important clues about evolutionary changes. To reveal these changes the large S. cryophilus supercontigs were assembled into chromosomes using synteny relationships and the conserved pericentromeric, subtelomeric genes. Togetherness of the supercontigs was confirmed by PCR. Investigation of the gene order revealed localisation of the rDNA arrays, more than 300 new conserved orthologues and proved that S. cryophilus supercontigs were mosaics of collinear blocks. PFGE analysis showed that size of the S. cryophilus chromosomes differ from the S. pombe chromosomes. Comparative genomic analyses of the newly assembled chromosomes confirmed that the closest relative of S. cryophilus was S. octosporus not just in sequence similarity but also in a structural way, and revealed that preservation of the conserved regions did not arise from the lower number of chromosomal rearrangements. Translocations were more typical in the closely related species, while the number of inversions increased with the phylogenetic distances. Our data suggested that sites of the chromosomal rearrangements were not random and often associated with repetitive sequences, structural- and nucleotide evolution might correlate. Chromosomal rearrangements of the fission yeasts compared to other lineages were also discussed.